P112: Cost of hypoglycemia associated with diabetes mellitus: a systematic review of the literature. (2nd June 2016) - Alexiu, C.; Kirkland, S.W.; Jelinski, S.; Chuck, A.; Campbell, S.; Rowe, B.H.
Abstract : Introduction: Diabetes mellitus (DM) is a major chronic disease. Many patients with DM suffer hypoglycemic episodes that may be mild, moderate or severe, requiring ambulance and emergency department (ED) services. The cost of these DM-associated hypoglycemic episodes in the ED is not well understood. This study identified literature on DM-associated hypoglycemia costs that were incurred in acute care settings, with particular interest in the ED setting.Methods: The methods of this systematic review were based on an a priori protocol. The literature searches involved 12 databases. Study selection and quality assessment were conducted independently by two reviewers. Costs from included studies were standardized to year 2014 Canadian dollars. Mean with standard deviation (SD) and median costs with interquartile range (IQR) were calculated whenever possible.Results: The systematic search yielded 1, 164 studies and 62 were included. The largest proportion of studies (45%) originated from USA data. Quality of included studies varied widely. Although none of the studies were purely a cost analysis of DM-associated hypoglycemia in the ED, 15 studies reported some ED costs. Median DM-associated hypoglycemic episode costs were 1, 187.15 in the ED and 1, 288.92 irrespective of setting. More severe episodes were more costly; costs were 8.5 times higher in the inpatient setting than in the ED. Episode costs were 18-45% higher for patients with Type 2 DM than Type 1. Direct costs comprised 80% of total costs.Conclusion: Acute episodes of DM-associated hypoglycemia are costly. These episodes also often require hospitalization; the highest costs are incurred by admitted patients with Type 2 DM. More studies are needed to better understand the costs associated with ED use by patients with DM-associated hypoglycemia.